Factors contributing to distress among school and college-going adolescents during COVID-19 Lockdown: A cross-sectional study conducted in Sibi Balochistan, Pakistan - Muhammad Azam Awais; Muhammad Minhaj Chaudhery; Muhammad Sarfraz Khan; Adam Umair Ashraf Butt; Abdur Rehman Malik; Muhammad Numair Khan; Areeb Khalid; Mohsin Mahmood; Mohammad Talal Afzal; Muhammad Haseeb Waseem (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Due to the COVID-19 pandemic, many countries have implemented nationwide lockdowns. While this leads to a decrease in disease transmission, there is a concurrent increase in the levels of psychological distress. To estimate the levels of psychological distress in school- and college-going adolescents currently under lockdown and to determine the factors associated with this psychological distress. MATERIALS AND METHODS: A cross-sectional study conducted in Army Public School and College (APSAC) Sibi, Balochistan province of Pakistan between March and May 2020. Students of APSAC Sibi were enrolled in this research. Modified Kuppuswamy Socioeconomic Scale, Godin Leisure-Time Exercise Questionnaire, and Kessler-10 were used for data acquisition. Chi-square and t-tests and univariate analysis (nonparametric test) were performed using the Statistical Package for the Social Sciences (SPSS) version 23.0 (IBM, Armonk, US). RESULTS: Out of 225 participants, 57.4% were studying at school. Sixty-four percent of the participants were likely to be suffering from psychological distress. There is a significant effect of physical activity, sleep duration, bedtime at night, screen-time duration, and COVID-19 positive family member on the levels of distress. A moderate positive correlation was between psychological distress and bed-time at night (rho[223] = 0.328, P < 0.001) and screen time duration (rho[223] = 0.541, P < 0.001). A moderate negative correlation of physical activity (rho[223] = −0.340, P < 0.001) and a weak negative correlation of sleep duration hours (rho[225] = −0.158, P = 0.018) was found with psychological distress levels. CONCLUSIONS: The COVID-19 lockdown and pandemic have had a considerable psychological impact on both school-going and college-going students, showing increased level of stress. A strong public health campaign along with mental and physical and social support programs are the need of the hour.